The Engineering of Plurilingualism Following a Blueprint for Multilingualism: The Case of Vanuatu's Education Language Policy. Issue 3 (16th August 2013) - Willans, Fiona
<x xml:space="preserve">Abstract</x> This article examines recent proposals in Vanuatu for a new, plurilingual education system. The article discusses these proposals with reference to three principles of plurilingualism upon which the proposals are ostensibly based: the need to value the linguistic repertoires with which children start school, the development of further linguistic resources to enhance individual potential, and the holistic integration of these resources within linguistic repertoires. The author argues that the proposals are driven not by concerns for the fostering of individual plurilingualism, but rather by an agenda of an imagined societal multilingualism within which certain languages are prioritised over all others. The result is an attempt to engineer plurilingual competence by following a blueprint for multilingualism, thus working against the needs of individuals. The article proposes a more flexible model of plurilingualism, within which teachers and learners have the freedom to negotiate meaning through whichever linguistic resources are available to them, rather than stipulating which languages should be used at any given time.